Waiting, Thinking, and Feeling: Variations in the Perception of Time During Silence - Pfeifer, Eric; Wittmann, Marc (Frontiers in Psychology, 2020)
Research on the perception of silence has led to insights regarding its positive effects on individuals. We conducted a series of studies during which individuals were exposed to several minutes of silence in different contexts. Participants were introduced to different social and environmental settings, either in a seminar room at a university or in a city garden, alone or in a group. Instructions across studies varied, as participants were exposed to real waiting situations, were asked to just think and to explicitly experience the time interval without further instructions or following a session of Depth Relaxation Music Therapy (DRMT)/ Hypnomusictherapy (HMT). Silence was judged to significantly increase relaxation, improve mood states, and alter the perception of time and the orientation towards the present moment. We controlled for influences of trait variables, such as impulsivity, mindfulness, daydreaming, and time perspective. Findings empirically demonstrate that exposure to silence can be effective in therapeutic and educational contexts to promote relaxation and well-being.